2007
DOI: 10.1002/ppul.20622
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte‐associated antigen‐4 gene polymorphisms confer susceptibility to atopic asthma in Korean children

Abstract: Summary. Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) is a negative regulator of T lymphocyte activation. The gene encoding CTLA-4 is a candidate gene for conferring susceptibility to allergic disease. The purpose of this study was to evaluate the potential effects of CTLA-4 gene polymorphisms in Korean children on asthma. We genotyped 272 children with atopic asthma, 54 children with nonatopic asthma (NAA), and 254 control children for allelic determinants at two polymorphic sites in the region at pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…One article reported two cohorts [34], and each cohort was considered as a separate case-control study. Finally, a total of 18 case-control studies in 17 articles were identified [15][17], [25][38], including 6378 cases and 8674 controls. There were 11 studies on +49 A/G, 12 studies on −318 C/T, 6 studies on −1147 C/T, 5 studies on CT60 A/G, 3 studies on −1722 C/T and rs926169.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One article reported two cohorts [34], and each cohort was considered as a separate case-control study. Finally, a total of 18 case-control studies in 17 articles were identified [15][17], [25][38], including 6378 cases and 8674 controls. There were 11 studies on +49 A/G, 12 studies on −318 C/T, 6 studies on −1147 C/T, 5 studies on CT60 A/G, 3 studies on −1722 C/T and rs926169.…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 studies of Asians [15], [17], [25][27], [29], [32], [34], [37], [38] and 6 studies of Caucasians [16], [28], [30], [31], [33], [36]. Five studies were performed in adults [15][17], [34], [38], 11 studies in children [25][27], [29]–[32], [34][37]. Two studies included both adults and juveniles [28], [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD86 [3], CD40 [4], CTLA4 [5,26], HLA-G [6], ICOS [7] and PDCD1 [8], yet other genes were found not to be associated with atopy such as CD28 [5] and LILRB4 [27]. A summary of these association studies is presented in table E4 of the supplementary material.…”
Section: Discussionmentioning
confidence: 99%